Women Religious and Sociopolitical Change in the Philippines, 1930s–1970s - Barry, Coeli (Archīum Ateneo, 2014)
Thisarticle develops a framework for the study of spirituality and the congregational lives of women religious in the Philippines from the 1930s to the early 1970s. It explores the multiple and sometimes contradictory meanings of membership of women in religious communities. Set within the history of women religious in the Catholic Church, the study explains the transformations in the originally Belgian order, the Immaculé Coeur Marie (ICM), while also drawing on the experiences of women leaders from other congregations. Thisarticle looks at the Filipinization of leadership and subsequent reshaping of congregational ideologies in the context of the Second Vatican Council and the Marcos regime.KEYWORDS: Church History • Nuns • Women’s History • Catholic Religious life • Politics and Catholicism in Asia